Multicultural Encounters - Sharma, S. author. aut Link
XIX, 224 p.
Keywords: This book confronts the challenge of difference for rethinking everyday multiculture. It proposes both a theory and practice of a critical pedagogy of popular culture through an analysis of contemporary media and film. For students and scholars committed to a critical practice for transforming the politics of representation and otherness.